2022
DOI: 10.3389/fendo.2022.961505
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationships between rheumatism and dyslipidemia: A two-sample Mendelian randomization study

Abstract: BackgroundDyslipidemia is often observed in rheumatic diseases, such as ankylosing spondylitis (AS), rheumatoid arthritis (RA), and systemic lupus erythematosus (SLE), yet it remains to be detected whether rheumatic diseases have a causal effect on dyslipidemia.MethodsSignificant (P < 5 × 10-8) and independent (r2 < 0.1) single-nucleotide polymorphisms in genome-wide association studies were selected as instrumental variables to conduct Mendelian randomization (MR) analysis. Inverse variance weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Importantly, their analysis did not suggest a causal link between RA and alterations in lipid factors. Zhang et al [ 34 ] used Genome wide association study data and demonstrated complex and sometimes contradictory relationships between lipid factors and RA. However, these analyses did not establish a causal link between RA and lipid factor alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, their analysis did not suggest a causal link between RA and alterations in lipid factors. Zhang et al [ 34 ] used Genome wide association study data and demonstrated complex and sometimes contradictory relationships between lipid factors and RA. However, these analyses did not establish a causal link between RA and lipid factor alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, CD36 is considered to be a crucial aspect of progression to liver steatohepatitis [90]. The increased fatty acid uptake and oxidation estimated in the livers of untreated AA rats indicate enhanced catabolic processes in the liver leading to cachexia and dyslipidaemia, as observed in arthritic animals [91] and RA patients [92]. The saffron extract, either with or without MTX, decreased CD36 gene expression (the lower dose significantly; the higher dose non-significantly), which might result in lower hepatic FA uptake and contribute to lipid homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The random effects IVW method uses a meta-analytical approach to combine the Wald ratios for the causal effects of each SNP and can provide the most precise estimates when all selected IVs are valid [ 31 , 32 ]. The weighted median method can provide a suitable causal assessment even if more than 50% of the IVs are ineffective [ 33 ]. The MR-Egger regression method provides an estimate corrected for multiple effects, but its main shortcoming is its lack of power [ 34 ].…”
Section: Methodsmentioning
confidence: 99%